Diarrhoea scores and weight changes in response to artificial milk supplementation or use of solulyte-neomycin solution in preweaning piglets - Chua, K. H.; Goh, Yong Meng; Lee, Y. H.; Law, Elizabeth Fang Lin (Veterinary Association Malaysia, 2005)

(untitled)
The objective of this study was to determine the effects of supplemental milk replacer and solulyte-neomix solution in preweaning piglets. A total of 199 five-day-old piglets from 22litters were available for this three-week study. 12 litters (110 piglets) were allocated into the milk replacer supplemented group (MILK), five litters (47 piglets) were allocated into the ELEC group which was given an antibiotic-fortified electrolyte solution for pigs, and five litters (45 piglets) remained as untreated control (CTRL). However, after matching for litter size and total litter weights among treatment groups, only 44 piglets (5litters) in the MILK group, 47 piglets (5 litters) in the ELEC group and 45 piglets from 5 litters in the CTRL group were considered in this report. All sows were fed the same diet (18 % protein, 3,952 kcal of ME/kg). Body weights of piglets were measured at days 5 and 25 of age. Fresh liquid commercial milk replacer and solulyte-neomix solution were prepared daily. The fluids were offered thrice daily at 100mL per litter for 5-day-old piglets. Supplementation was increased to 5 times daily at 200mL per litter when piglets were 9 days or older, till the end of the trial. Average litter weight gain was higher in the ELEC piglets given solulyte-neomix solution and creep feed (P<0.05). Milk replacer supplemented group (MILK) generally had lower average litter weight gains at 3.72 kg. However, the diarrhea scores were affected by the types of supplementation fluids given. The overall diarrhoea scores were higher in the MILK and CTRL piglets compared to the ELEC piglets. In conclusion, milk replacer supplementation offered no obvious benefit in terms of weight gain, final weight, and overall diarrhoea scores in piglets compared to solulyte-neomix supplemented piglets.